Exploring the Effects of Oil and Gas Prices on Industrial Production in Colombia: A Quantile Regression Analysis - Candelo-Viafara, Juan Manuel; Oviedo-Gomez, Andres; Rivera-Diaz, Maria Del Pilar (International Journal of Energy Economics and Policy, 2023)
This study examines the impact of oil and gas prices on industrial production in Colombia between 1997 and 2022 using the quantile regression methodology (QR) to evaluate seasonality and nonlinear effects on the distribution of the industrial sector, the findings indicate that when industrial production is at low levels, fluctuations in gas prices have minimal impact. Conversely, when industrial production is at medium levels, gas prices have a significant negative impact, while at high levels (above the sixth decile), gas prices have a negative but not significant impact. On the other hand, oil prices generate positive and significant impacts at medium and high production levels. The study concludes that increasing gas production in the country would lead to a reduction in its price, decrease costs, and increase national production, additionally, gas production can be a viable element in energy transition, as it strengthens sectors of the economy other than oil.